Landscape Design as the Representation of Relationships with Nature, Ecologies and Other Living Species (diségno, 2024)
Landscape design has always been considered an open reference, an available space of interpretation, but this is not equivalent to considering it a field of indeterminate images and concepts [Caravaggi 2021].The hypothesis I will attempt to argue in this article is that landscape design can be coherently interpreted as a representation of the infinite relationships between human societies and the natural world and, more recently, between humans and other living species. [read more]